The mobile health application can add our insight into caring for children: The benefit and future usage of the Chemo Assist for Children - Dwi Novrianda; Rika Sarfika (JKP (Jurnal Keperawatan Padjajaran), 2023)
Background: The ease of use of mobile health applications felt by users is essential to ensure the sustainability of digital-based intervention programs. The mHealth Chemo Assist for Children (CAC) application has been used by parents with children with acute lymphoblastic leukemia (ALL) who are undergoing chemotherapy in usability tests and positive benefits felt by users have been reported. A deeper understanding of the barriers and factors supporting implementing the CAC mHealth application can help guide strategies to overcome these challenges.